Perspectives of lowering CUORE thresholds with Optimum Trigger. (December 2020) - Dompè, V; Adams, D Q; Alduino, C; Alfonso, K; Avignone, F T; Azzolini, O; Bari, G; Bellini, F; Benato, G; Bersani, A; Biassoni, M; Branca, A; et al.
Abstract: CUORE is a cryogenic experiment that focuses on the search of neutrinoless double beta decay in 130Te and it is located at the Gran Sasso National Laboratories. Its detector consists of 988 TeO2 crystals operating at a base temperature of ∼10 mK. It is the first ton-scale bolometric experiment ever realized for this purpose. Thanks to its large target mass and ultra-low background, the CUORE detector is also suitable for the search of other rare phenomena. In particular the low energy part of the spectra is interesting for the detection of WIMP-nuclei scattering reactions. One of the most important requirements to perform these studies is represented by the achievement of a stable energy threshold lower than 10 keV. Here, the CUORE capability to accomplish this purpose using a low energy software trigger will be presented and described.